FIZIČKA AKTIVNOST I ZDRAVLJE - Slobodan Stojiljković; Slavica Stojiljković; Ljubica Andrejić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The knowledge about wide preventive and therapy healt effects of attaining and keeping the average level of aerobic capability, are considered as significant accomplishment of modern medicine. Namely, their practicale application, wich is, supervised by educated experts, very simple, healty safe, and doesent require any matirial costs, and more favorable rezults can be expected rather than any other medicine or preventive remedy application. The necessery prerequisite for physical activities using are anantification and qualification of both physical activites conserning healt purpose, the intensiti of phisical effort is dozed on the basis of previously determined level of physical ability. At the persons with expressed if the level of aerobic ability, through spreading the healt, programmed practising exellent results in many chronical uninfected diseases prevention, can be achivied.Programmed physical activity, directed to the increasing of aerobic ability, gives significant treatment effect at some chronical uninfect diseases such as. coronary diseases, myocardditis, infartc, hypertension, corpulence, diabetes etc